Three phase oil-immersed distribution transformers, 50 Hz, from 50 to 2500 kVA with highest voltage for equipment not exceeding 36 kV. Supplementary requirements for transformers with highest voltage for equipment equal to 36 kV Part 3, (15th September 1995) - British Standards Institution,
No abstract available